2006
DOI: 10.1158/0008-5472.can-06-0732
|View full text |Cite
|
Sign up to set email alerts
|

Mutation Accumulation in the Intestine and Colon of Mice Deficient in Two Intracellular Glutathione Peroxidases

Abstract: Mice deficient in two glutathione peroxidases (GPX), Gpx1 and Gpx2, [Gpx1/2-double knockout (DKO) mice] are prone to ileocolitis on a mixed C57BL/6 and 129S1/SvJ (B6.129) genetic background. We reported previously that f25% of B6.129 Gpx1/2-DKO mice develop ileocolonic tumors by 6 to 9 months of age, when their non-DKO littermates [having at least one wild-type (WT) Gpx1 or Gpx2 allele] rarely have inflammation and none have tumors. Because genetic background affects tumor susceptibility, we have generated a B… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 43 publications
2
31
0
Order By: Relevance
“…Conversely, selenium, the essential constituent of protective enzymes, prevents tumor development in rats submitted to chemical carcinogenesis [50]. Lack of protective systems in knockout mice such as lack of peroxiredoxin or glutathione (GSH) peroxidases indeed leads to malignant cancers [51,52]. Transfection of an H2O2-generating system transforms epithelial cells [53].…”
Section: Toxic Effects Of H2o2mentioning
confidence: 99%
“…Conversely, selenium, the essential constituent of protective enzymes, prevents tumor development in rats submitted to chemical carcinogenesis [50]. Lack of protective systems in knockout mice such as lack of peroxiredoxin or glutathione (GSH) peroxidases indeed leads to malignant cancers [51,52]. Transfection of an H2O2-generating system transforms epithelial cells [53].…”
Section: Toxic Effects Of H2o2mentioning
confidence: 99%
“…Interestingly, transgenic mice lacking i 6 A in Sec tRNA [Ser]Sec display decreased liver and colon GPX1 expression, and show increased azoxymethane-induced aberrant crypts in the colon [Irons et al, 2006]. Moreover, there is an accelerated accumulation of mutations in the colon of GPX1 and GPX2 double knockout mice [Lee et al, 2006]. Furthermore, GPX1 expression is decreased in estrogen receptor-positive breast cancer cells [Esworthy et al, 1995] and in the PC-3 prostate cancer cell line, which has been reported to possess a defective BER response [Trzeciak et al, 2004].…”
Section: Seleniummentioning
confidence: 99%
“…It is known that selenoenzymes are fundamental for redox homeostasis. GPx1 knockout mice are more vulnerable to oxidative stress [15,16], GPx1/GPx2-double-knockout mice have a trend to develop cancer [17], knockout of PHGPx causes early embryonic lethality [18,19], and knockout of TrxR results in embryonic lethality [19]. Therefore, when cells are in a Se deficient state, the avidity of Se uptake mechanisms may be increased to maintain the biosynthesis of selenoenzymes.…”
Section: Introductionmentioning
confidence: 99%